2018
DOI: 10.19173/irrodl.v19i3.3482
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Flipped Classroom Model on Students' Academic Achievement

Abstract: The aim of this study is twofold. First, it aims to investigate the impact of the Flipped Classroom (FC) Model on students’ academic achievement. Second, it reveals the students’ opinions about the model itself. For four weeks, the students in the experimental group were taught in a blended learning context where the FC Model was applied, while the lessons in the control group were carried out through traditional blended learning. Both groups were administered a test before and after the Flipped Classroom sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
5
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 27 publications
6
97
5
13
Order By: Relevance
“…[18] Conversely though, the results of our study showed a significant difference in the performance among the FC group.…”
Section: Discussioncontrasting
confidence: 54%
“…[18] Conversely though, the results of our study showed a significant difference in the performance among the FC group.…”
Section: Discussioncontrasting
confidence: 54%
“…These characteristics require students to assume a more responsible and proactive role during their learning experience in order to improve their academic performance. Most of the Faculties of Education, specifically in the field of future teachers' training, do not analyze the results of this method at the final stage, though (Zainuddin and Hajar 2016;Lundin et al 2018;Cabi 2018). Horn and Staker (2014) refer to the rotation model, and within it the flipped classroom sub-model, which consists of a new approach in which the class is inverted in order to change the traditional working time perspective in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the models extend time to dedicate to classroom discussions which provides students with more purposeful speaking and writing practice, they increase both the quantity and quality of teacher-student and student-student collaboration and students' academic performance. The latter was experimentally proved by Zhonggen & Wang (2016) when delivering the courses in English writing and by Cabi (2018), who used a "flipped classroom" model in English Language Teaching and Turkish Language Teaching Programs.…”
Section: The "Flipped Classroom" and Multimedia Textbookmentioning
confidence: 95%
“…Form the instructional perspective, scientists report that the "flip classroom" model satisfies their pedagogical needs. While Findlay-Thompson & Mombourquette (2014, p. 65) stated flipped course met their needs in "application, analysis, and evaluation", Wiginton (2013) and Cabi (2018) asserted that the model accelerates student responsibility, motivation, self-organisation, and the skills of research-based and autonomous learning.…”
Section: The "Flipped Classroom" and Multimedia Textbookmentioning
confidence: 99%